Trend of learning, social and ethical behaviours in the use of mobile wireless technology (MWT) in learning at International Islamic University Malaysia - Syaza Hazirah binti Mohd Hashim (Kulliyyah of Education, International Islamic University Malaysia, 2015)
With the increasing numbers of mobile subscriber per year, researchers are now considering the benefit of Mobile Wireless Technology (MWT) in assisting students' learning. In addition to its technological affordances and its lightweight nature, mobile learning (mLearning) is expected not only to improve but also to evolve the culture of learning among students in line with the 21st century technology. The main objective of the study was to investigate students' social communication trend as well as the extent of the use of their personal MWT for educational purposes. The second objective of the study was to explore the differences between gender on the aspects of (i) mLearning, (ii) Ethical behaviour; and (iii) Social behaviour. The third objective for the study was to predict the ethical and social behaviours on influencing the existing mobile learning (mLearning) environment among the higher learning students. A survey was carried out in International Islamic University Malaysia (IIUM) from a stratified sampling where each stratum has been sampled as an independent sub-population. The stratum involved four Kulliyahs namely: Kulliyah of Education (KOED), Kulliyah of Engineering (KOE), Kulliyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS) and Kulliyah of Information and Communication Technology (KICT). There were 340 respondents involved in the study. The descriptive analysis was used to address the first research question, “What is the social communication trend of Mobile Wireless Technology (MWT) usage among higher learning students based on Gender”, whereas Independent T-Test was employed to the second research question “To what extend do higher learning students use Mobile Wireless Technology (MWT) for learning.” Due to multiple variables, analysis of variance (ANOVA) has been used to analyse the third research question “Are there any differences between gender on the following aspects of (i) mLearning, (ii) Ethical behaviour; and (iii) Social behaviour”. Multiple regression analysis (MRA) has been used to address the fourth research question Do ethical behaviour and social behaviour influence students' mobile learning. Findings show significant influence of ethical behaviour and social behaviour on students' mLearning. Thus, it is necessary for behaviour guidelines to be exposed to the student to enable mLearning to be executed effectively in the formal education setting.